THE SIGNIFICANCE OF LEARNING ENGLISH IN THE GLOBALIZED WORLD (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
In the modern world, learning English provides valuable opportunities for communication  . As the primary language of unversal business, trade, and diplomacy, it fasilitate individuals to connect with people from various cultural backgrounds. Proficiency in English improve communication skills, expands professional connections, and grants entrance to a vast range of information and resources. Additionally, it makes traveling more convenient, as English is widely spoken in many countries, allowing for easier interaction with locals and navigation of new places.